Impact of the Ingestion of Plastic Waste in Fish - Escobar Condor, Edward Werner (2020)
The present research corresponds to a review on the investigations carried out based on the exposure of a diversity of fish to different concentrations and types of plastic waste, either through direct intake, exposure to contaminated environments or by transferring them through the trophic chain. In the development, a description of the types and degrees of affectations that this waste causes to the fish is presented; likewise, a comparison of the results obtained by some authors in their experiments has been included. As a result of the analysis carried out, it has been concluded that the waste is easily assimilated by fish, regardless of their size and that due to their small size, microplastics act as aquatic vectors capable of transporting organic and inorganic materials on their surface to cause potential damage to marine organisms that absorb them directly or indirectly.